2002
DOI: 10.1002/humu.9045
|View full text |Cite
|
Sign up to set email alerts
|

Identification of fifteen novel mutations in the SLC12A3 gene encoding the Na-Cl Co-transporter in Italian patients with Gitelman syndrome

Abstract: The SLC12A3 gene encodes the thiazide-sensitive Na-Cl co-transporter (NCCT) expressed in the apical membrane of the distal convoluted tubule of the kidney. Inactivating mutations of this gene are responsible for Gitelman syndrome (GS), a disorder inherited as an autosomal recessive trait. We searched for SLC12A3 gene mutations in 21 Italian patients with the clinical and biochemical features of GS (hypokalemia, hypomagnesemia, metabolic alkalosis, hypocalciuria, and the absence of nephrocalcinosis). All coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 12 publications
4
40
0
Order By: Relevance
“…In the present study the specific involvement of this cotransporter in the etiology of this disorder is further substantiated by the finding that the proband is homozygous for the S615L variation. The S615L identified in this study was previously described by Cruz and co-workers [18] in a study involved 36 kindreds from the United States, Canada and England and later reported in a study by Syrén et al [22]. Although the SLC12A3 variations reported in previous studies are distributed throughout the whole protein [4,23], the study of Lemmink (1998) indicates that the carboxyterminal end represents a hot spot for variations [4].…”
Section: Discussionsupporting
confidence: 59%
“…In the present study the specific involvement of this cotransporter in the etiology of this disorder is further substantiated by the finding that the proband is homozygous for the S615L variation. The S615L identified in this study was previously described by Cruz and co-workers [18] in a study involved 36 kindreds from the United States, Canada and England and later reported in a study by Syrén et al [22]. Although the SLC12A3 variations reported in previous studies are distributed throughout the whole protein [4,23], the study of Lemmink (1998) indicates that the carboxyterminal end represents a hot spot for variations [4].…”
Section: Discussionsupporting
confidence: 59%
“…In addition, we included one further variant in NCCT found once in FHS, R861C, which has previously been reported as disease-causing 23,24 and was found in 4 of our European Caucasian GS subjects (homozygous in 1). This non-conservative substitution is at a position conserved among all vertebrates.…”
Section: Mutations In Slc12a1 Slc12a3 and Kcnj1 In Fhsmentioning
confidence: 99%
“…Human eGFP-NCC cotransporter function was determined by assessing tracer 22 Na + uptake (PerkinElmer Life Sciences, Groningen, The Netherlands) in groups of 25 oocytes following a standard protocol of 30 min of incubation in a Cl À -free ND96 medium containing 1 mM ouabain, 0.1 mM amiloride and 0.1 mM bumetanide, following 1 h of uptake in K + -free, NaCl medium (40 mM NaCl, 56 mM sodium-gluconate, 4 mM CaCl 2 , 1 mM MgCl 2 and 5 mM Hepes/Tris, pH 7.4) containing 1 mM ouabain, 0.1 mM amiloride, 0.1 mM bumetanide and 2 m Ci of 22 Na + /ml. 20 As a control, one group of waterinjected oocytes has been included to determine the basal unspecific tracer 22 Na + uptake in all experiments.…”
Section: Na + Transport Assaysmentioning
confidence: 99%
“…20 As a control, one group of waterinjected oocytes has been included to determine the basal unspecific tracer 22 Na + uptake in all experiments.…”
Section: Na + Transport Assaysmentioning
confidence: 99%
See 1 more Smart Citation